The Influence of Teacher Discipline Dimensions on the Quality of the Teaching and Learning Process at MIS Al-Hilal Wanakarta School, Lolong Guba District, Buru Regency - Iis Amalia; Mohamad Arsad Rahawarin; Julia Theresia Patty (Journal of International Multidisciplinary Research, 2025)
The purpose of this study is to determine how the quality of teaching and learning process at Mis Al-Hilaal Wanakarta school is impacted by the aspects of teacher discipline. This study employs quantitative approach and uses saturated sample which involves twelve teachers. The data is gathered by observation, questionnaires with five possible answers on a Likert scale score choice form that are distributed to twelve teachers, and documentation as a supplementary method. The data is analyzed using a straightforward linear regression test that includes Spearman rank correlation and the determination coefficient test, t test, or partial test, and F test, or simultaneous test. According to the study's findings, (H_0)  is rejected and (Ha) is accepted, indicating a strong and positive relationship between the aspects of teacher discipline and the quality of teaching and learning process. This is supported by the Spearman rank correlation coefficient value of 0.6137. Based on the R Square value of 0.517 obtained from the simple linear regression test, there is a 51.7% impact of the teacher discipline aspects on the quality of teaching and learning process. The results of the t test shows that the variable aspects of teacher discipline have a significant impact on the quality of the teaching and learning process (t value (3.269) > t table (1.812) with a significance of 0.008 <0.05), and the results of the F test shows that the F value is 10.683 with a significance of 0.008 <0.05.